MENINGKATKAN KEMAMPUAN BERBICARA SISWA SMA DENGAN MENGGUNAKAN PERMAINAN TRUTH OR DARE: IMPROVING SPEAKING ABILITY OF SENIOR HIGH SCHOOL STUDENTS BY USING TRUTH OR DARE GAME - Lestari, Dinda Sri; Harahap, Fitri Handayani; Husniah, Nabilatul; Ihsan, Muhammad Taufik (AUFKLARUNG: Jurnal Kajian Bahasa, Sastra Indonesia, dan Pembelajarannya, 2023)
The purpose of the study is to learn how Truth or Dare games affect the teaching of speaking skills and to explain how communication games affect students' speaking skills. You may have memories of who used the bottle to be "it" and then chose the embarrassing dare. But the most important thing to remember is how much fun this game is and how much fun it is. And when you play it in ESL class, it's just as fun for your students. All that is required to play this game is a bottle that the student can rotate to determine who is the questioner and who is asked. And best of all, it can be adapted to any class and any language level. Therefore, the criteria for success have been determined. It is important to note that communication games have a positive impact on teaching the learning process.